Pelatihan Penyuntingan Artikel Bebas di Wikipedia bagi Siswa SMAN 1 Indralaya Utara - Erina, Lili; Saptawan, Ardiyan; Alamsyah; Martina; Ikhsan, Diyaz S.; Purnamasari, Ayu (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This service activity aims to increase knowledge and provide practical experience in editing free texts in Wikipedia for students of North Indralaya 1 High School located in Ogan Ilir District, South Sumatera Province. This service activity involved 30 participants who were selected purposively and came from 11th Class. Apart from gaining conceptual knowledge about writing, the psychology of writing, and the Wikipedia ecosystem, the participants were also given technical knowledge about the procedures for editing manuscripts on Wikipedia. This service activity which lasted for three days can increase the participants' knowledge significantly. The service team recommended that the school to build collaborate with Wikipedia to increase writing intensity among students.